Mine Water Problems Of The Pennsylvania Anthracite Region - H. A. Dierks (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1957)
PENNSYLVANIA's anthracite region lies in the heart of the richest and most densely populated area of the U. S. Nearly 70 million people live within a radius of 500 miles, in which 130,000 manufacturing plants employ more than 8 million workers. The region comprises some 3000 sq miles and contains 484 sq miles of coal measures, which folding and erosion have divided into four separate and distinct fields, known as the Northern, Eastern Middle, Western Middle, and Southern.